Advances in biologic augmentation for rotator cuff repair. Issue 1 (17th October 2016) - Patel, Sahishnu; Gualtieri, Anthony P.; Lu, Helen H.; Levine, William N.
Abstract : Rotator cuff tear is a very common shoulder injury that often necessitates surgical intervention for repair. Despite advances in surgical techniques for rotator cuff repair, there is a high incidence of failure after surgery because of poor healing capacity attributed to many factors. The complexity of tendon‐to‐bone integration inherently presents a challenge for repair because of a large biomechanical mismatch between the tendon and bone and insufficient regeneration of native tissue, leading to the formation of fibrovascular scar tissue. Therefore, various biological augmentation approaches have been investigated to improve rotator cuff repair healing. This review highlights recent advances in three fundamental approaches for biological augmentation for functional and integrative tendon–bone repair. First, the exploration, application, and delivery of growth factors to improve regeneration of native tissue are discussed. Second, applications of stem cell and other cell‐based therapies to replenish damaged tissue for better healing are covered. Finally, this review will highlight the development and applications of compatible biomaterials to both better recapitulate the tendon–bone interface and improve delivery of biological factors for enhanced integrative repair.